Effect of 6-benzylaminopurine, naphthaleneacetic acid and activated charcoal on rose micropropagation using nodal explants - Abdallah, Hala M (Gezira Journal of Agricultural Science; Vol 12 No 1 (2014), 2014)
Rose is one of the most important commercial flower crops. It is used in the floriculture and cut flower industry, perfume, cosmetic and medicinal purposes in many regions of the world. Conventional methods of rose propagation are slow with a low percentage of success. The objective of this study was to develop a protocol for in vitro propagation of rose, cv. Sara, using nodal explants. Three experiments were conducted during 2012.  In the first experiment, the effects of different concentrations of  6-benzylaminopurine (BAP) (0.0, 1.0, 2.0, 3.0, 4.0 and 5.0 mg/l) were tested on nodal explants of rose, cv. Sara. Different concentrations of naphthaleneacetic acid (NAA) (0.0, 0.1, 0.2 and 0.4 mg/l) combined with 1.0 mg/l BAP were tested in the second experiment. Factorial combinations between BAP at 0.0, 1.0 and 2.0 mg//l and activated charcoal (AC) (0.0 and 3.0 g/l) were tested. Completely randomized design was used in this study with five replicates and four explants per replicate. BAP at 1.0 mg/l was the best concentration for in vitro morphogenesis of rose, cv. Sara. The results showed that combinations of NAA with 1.0 mg/l BAP significantly reduced the number of shoots per explant. Addition of AC to MS medium devoid from BAP increased the number of shoots. BAP at 1.0 mg/l without AC was the best for shoot multiplication. AC with 2.0 mg/l BAP resulted in the maximum number of roots per plantlet. الورد الإنجليزي هو أحد أهم نباتات الزينة الاقتصادية المستوردة. يستخدم الورد الإنجليزي كنبات مزهر في تنسيق الحدائق و كأزهار للقطف و العطور و ادوات التجميل و الأغراض الطبية في كثير من أنحاء العالم. طرق الإكثار الخضري التقليدية للورد الإنجليزي بطيئة و نسبة نجاحها ضعيفة في مواسم محددة. الهدف من هذه الدراسة هو تطوير تقنية للإكثار الدقيق للورد الإنجليزي الصنف سارا باستخدام العقد الساقية. أجريت ثلاث تجارب في هذه الدراسة في العام 2012. في التجربة الأولي تمت دراسة تأثير ستة تراكيز هي  (٬0.0 ٬1.0 ٬2.0 ٬3.0 4.0 و 5.0 ملجم| لتر) من 6 - بنزايل أمينوبيورين ((BAP . في التجربة الثانية تم اختبار أربعة تراكيز هي (٬0.0 ٬0.1 ٬0.2 و 0.4 ملجم| لتر)  من حمض خلات النفثالين   (NAA ) بالاتحاد مع 1 ملجم| لتر BAP. في التجربة الثالثة تم اختبار ثلاثة تراكيز هي(0.0, 1.0 و 2.0 ملجم| لتر) BAP مع تركيزين  0.0 و 3.0 جرام| لتر من  الفحم النباتي. استخدم التصميم العشوائي الكامل في هذه الدراسة بخمس  مكررات و أربعة عقد ساقية في كل مكرر. اوضحت الدراسة أن 1.0 ملجم| لتر من  BAP هو أفضل تركيز لمقاييس النمو الخضري للصنف سارا. اتحاد NAA مع 1.0 ملجم| لتر من  BAP أدي إلي انخفاض معنوي في عدد الأفرع (النموات الخضرية) لكل عقدة ساقية. إضافة الفحم النباتي الي وسط موراشيجي و سكوق الخالي من BAP أدي إلي ارتفاع عدد النموات الخضرية. كان 1.0 ملجم| لتر BAP من غير فحم نباتي الأفضل لتضاعف النموات الخضرية. كان  الفحم النباتي مع  2.0ملجم/لتر الأفضل للحصول علي أعلي عدد من الجذور لكل عقدة ساقية.